Evaluating the Allelopathic Effects of Salvia rosmarinus on Selected Weeds and Triticum aestivum L. - SIRWA QADIR (Al-Qadisiyah Journal For Agriculture Sciences)
Allelopathic effects of Rosmarinus officinalis (rosemary) have been investigated on 3 weeds: Vicia sativa, Vicia ervila, Hordeum spontaneum and one important cereal crop Triticum aestivum L. (bread wheat). A Laboratory experiment was laid out and 0.00, 1.00, 1.50 and 2.00 mg/ ml solutions of the ethanolic leaf extract were applied each with 5 replications. After 2 weeks, several germination indices and seedling growth characters were recorded. The chemical constituent of the extract was identified with GC–MS analysis. Eucalyptol, camphor, terpinene, linalool, ferruginol were identified as a dominant allelochemicals. A significant decrease was recorded in the germination % (G %) and germination velocity (GV) of Vicia ervilia, Vicia sativa and Hordeum spontaneum. While, seedling vigor index (SVI) was decreased significantly in Hordeum spontaneum and Triticum aestivum L. Although, a significant increase observed only in the root and shoot length of Triticum aestivum L., but it decreased significantly in the other parameters. A significant reduction in the seedling biomass of Vicia ervilia and Hordeum spontaneum was recorded. A remarkable increase was recorded in the seedling moisture content of Hordeum spontaneum and Triticum aestivum L. Generally, it can be concluded that rosemary exhibited a negative allelopathic effects on the weeds that can be used as a herbicide, but a positive promoter effect on Triticum aestivum L.